2023
DOI: 10.3390/v15020477
|View full text |Cite
|
Sign up to set email alerts
|

Using Multiplex Amplicon PCR Technology to Efficiently and Timely Generate Rift Valley Fever Virus Sequence Data for Genomic Surveillance

Abstract: Rift Valley fever (RVF) is a febrile vector-borne disease endemic in Africa and continues to spread in new territories. It is a climate-sensitive disease mostly triggered by abnormal rainfall patterns. The disease is associated with high mortality and morbidity in both humans and livestock. RVF is caused by the Rift Valley fever virus (RVFV) of the genus Phlebovirus in the family Phenuiviridae. It is a tripartite RNA virus with three genomic segments: small (S), medium (M) and large (L). Pathogen genomic seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In an interesting paper, Juma et al [ 11 ] reported the development of a new amplicon multiplex PCR-based method for the genome surveillance of segmented RNA viruses. The use of this alternative method can help the faster identification of virus outbreaks, leading to faster responses without the need for virus cell culture enrichment.…”
mentioning
confidence: 99%
“…In an interesting paper, Juma et al [ 11 ] reported the development of a new amplicon multiplex PCR-based method for the genome surveillance of segmented RNA viruses. The use of this alternative method can help the faster identification of virus outbreaks, leading to faster responses without the need for virus cell culture enrichment.…”
mentioning
confidence: 99%